Study on adsorption of some metals from waste solution by (unsaturated polyester-kaolin) composite - Raghad Hamid Hilal; Rafah Alwan Nassif (Kuwait Journal of Science)
In the current study (unsaturated polyester-kaolin) composite material was prepared with 5% clay loading (5 ​g) of e-waste was dissolved in diluted HNO3 (1:1) to prepare a neutral e-waste solution. The extraction process was used to remove Pb2+ and Cu2+ from e-waste by the adsorbent composite material under different contact times (40,60, 100, 140, and 180 ​min). The efficiency and adsorption capacity of the composite material increased with time and were nearly stable after 100 ​min. The test results showed the maximum value at 180 ​min of adsorption efficiency was 45.7% and 16.02%, adsorption capacity was 10.231 ​μg/g and 2.869 ​μg/g, and the removal 54.4% and 45.3% for copper and lead ions, respectively.